Sticky Platelet Syndrome - Kubisz, Peter; Stasko, Jan; Holly, Pavol (Seminars in Thrombosis and Hemostasis, 2013)
Sticky platelet syndrome (SPS) is a thrombophilic thrombocytopathy with familial occurrence and autosomal dominant trait, characterized by an increased in vitro platelet aggregation in response to low concentrations of adenosine diphosphate (ADP) and/or epinephrine (EPI). According to aggregation pattern, three types of the syndrome can be identified (hyperresponse after both reagents, Type I; EPI alone, Type II; ADP alone, Type III). Clinically, the syndrome is associated with both venous and arterial thrombosis. In pregnant women, complications such as fetal growth retardation and fetal loss have been reported. The first thrombotic event usually occurs before 40 years of age and without prominent acquired risk factors. Antiplatelet drugs generally represent adequate treatment. The use of other antithrombotics is usually ineffective and may result in the recurrence of thrombosis. In most patients, low doses of antiplatelet drugs (acetylsalicylic acid, 80–100 mg/d) lead to normalization of hyperaggregability. Combination of SPS with other thrombophilic disorders has been described. Despite several studies investigating platelet glycoproteins' role in platelets' activation and aggregation, the precise defect responsible for the syndrome remains unknown. The aim of this review is to summarize authors' own experience about SPS and the clinical data indexed in selected databases of medical literature (PubMed and Scopus).
Keywords: sticky platelet syndrome; platelet hyperaggregability; thrombophilia; platelet disorders